Chemical composition, antimicrobial and antifungal activity of Lippia Thymoide essential oil in oral pathogens - Tabata Resque Beckmann Carvalho; Erich Brito Tanaka; Amujacy Tavares Vilhena; Paula Cristina Rodrigues Frade; Ricardo Roberto de Souza Fonseca; Tânia Maria de Souza Rodrigues; Mileide da Paz Brito; Sebastião Gomes Silva; Raul Nunes de Carvalho Junior; Mozaniel Santana de Oliveira; Eloisa Helena de Aguiar Andrade; Aldemir Branco Oliveira-Filho; et al. (Universidade Estadual de Campinas, 2021)
Aim: This study evaluated the chemical composition of Lippia thymoides (Lt) essential oil and its antimicrobial activity against fungal strains of Candida albicans (Ca) and Gram-negative bacteria Prevotella intermedia (Pi) and Fusobacterium nucleatum (Fn). Methods: Lt essential oil was obtained by hydrodistillation apparatus with a modified Clevenger extension. The chemical analysis was analyzed by gas phase chromatography and mass spectrometry on Shimadzu QP 2010 plus. Sample sensitivity evaluation was performed by ABHb-inoculum and culture plates were developed with triphenyltetrazolium chloride, also Fn and Pi samples analysis were in anaerobic environment and Ca sample analysis was performed in aerobic environment. The minimum inhibitory concentration (CIM) was determinated by microdilution in eppendorfs tubes. Results: The chemical analysis showed that Thymol (59,91%) is the main compound found in Lt essential oil, also other antifungal and antimicrobial agents were present γ-terpinene (8.16%), p-cymene (7.29%) and β-caryophyllene (4.49%), Thymol is a central ingredient of many medicinal plants and has a potent fungicidal, bactericidal and antioxidant activity, it has been previously shown to have anti-inflammatory activity against Periodontal Disease (PD) cause can reduces prostanoids, interleukins, leukotrienes levels in periodontium. CIM result Pi was 6.5 μg/mL, Fn was 1.5 μg/mL and Ca was 0.19 μg/mL. Conclusion: The antimicrobial activity of L. thymoides, through the compound Thymol, has been shown promising potential against gram-negative periodontopathogenic bacteria and fungi whose therapeutic arsenal is still very restricted.